PERAN PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KECERDASAN EMOSIONAL SISWA DI SD PATRA DHARMA BALIKPAPAN - Sri Rahmadani; Iskandar Yusuf (Sindoro: Cendikia Pendidikan, 2025)
Education not only aims to enhance students' emotional intelligence but also to shape good character and morals. Therefore, the role of Islamic Religious Education teachers is very important in shaping the intelligence of students at school. This study aims to identify the contribution of Islamic Religious Education teachers in shaping the intelligence of students at SD PATRA DHARMA 1 Balikpapan. By using a field research approach and qualitative methods, data were collected through observation, interviews, and documentation, and then analyzed to draw conclusions. Research results showing: 1) PAI teachers play an important role in shaping students' emotional intelligence, which is manifested through the habituation of religious activities at school. 2) The PAI teacher's strategy includes habituating various religious activities to support the development of students' emotional intelligence. 3) The development of students' emotional intelligence is already good, as seen from their habit of engaging in religious activities, although some students still need further guidance. 4) The solution used to address the obstacles faced is through an approach and discussion with other subject teachers, homeroom teachers, and guidance counselors.